2014
DOI: 10.1007/s12306-014-0311-6
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and its relationship with osteoarthritis: risk factor or direct consequence?

Abstract: We cannot support neither the thesis of a direct effect of sarcopenia on OA development nor the opposite relation, because the up-to-date literature lacks basic science studies concerning these topics. The absence of clinical studies regarding measurements and tools to compare sarcopenia and OA do not allow to definitely clarify this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
0
42
1
Order By: Relevance
“…The degenerative effects of muscle atrophy can be seen with both acute and chronic MSK injuries that result in prolonged treatment or muscle immobilisation, such as fractures and ligament injuries 1. Loss of strength is a major risk factor for osteoarthritis (OA),2 3 the most common MSK disease responsible for reduced function3 and quality of life of sufferers,4 affecting around 250 million adults worldwide5 with a prevalence correlating with the increasing age of the population 6. Muscle weakness is increasingly evident in non-injured healthy populations such as older adults due to sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…The degenerative effects of muscle atrophy can be seen with both acute and chronic MSK injuries that result in prolonged treatment or muscle immobilisation, such as fractures and ligament injuries 1. Loss of strength is a major risk factor for osteoarthritis (OA),2 3 the most common MSK disease responsible for reduced function3 and quality of life of sufferers,4 affecting around 250 million adults worldwide5 with a prevalence correlating with the increasing age of the population 6. Muscle weakness is increasingly evident in non-injured healthy populations such as older adults due to sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…One systematic review article criticized that the literature lacks basic science studies and that it could not be concluded whether sarcopenia has a direct effect on OA [15]. The more direct effect of sarcopenia on knee OA should be shown by a skeletal muscle mass analysis that focuses on the lower limbs as well as analyses that include a multivariate regression model because there are several risk factors of knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of extracellular matrix (ECM) production leads to a progressive loss of cartilage volume [4,5].…”
Section: Histological Abnormalitiesmentioning
confidence: 99%
“…Age, overuse syndromes, obesity, menopause, sarcopenia, macro-and micro-traumatic iterative events are the main risk factors for the onset of chondropenia [3,4]. Prerequisite for an etiological approach is knowledge of the multifactorial aspects such as genetic, hormonal and biomechanical factors which converge in the manifestation of the chondropenic phenotype and are useful parameters for identifying the patients at risk for disease progression.…”
Section: Etiologymentioning
confidence: 99%